MicroRNA-29b-3p aggravates 1, 2-dichloroethane-induced brain edema by targeting aquaporin 4 in Sprague-Dawley rats and CD-1 mice. (1st February 2020) - Zhong, Yizhou; Liang, Boxuan; Hu, Manjiang; Liu, Jun; Lin, Li; Jiang, Junying; Lin, Xi; Huang, Yuji; Lu, Lvliang; Jiang, Liang; Wu, Jiejiao; Jia, Xiaohui; et al.
Highlights: 1, 2-DCE exposure induces brain edema through down-regulation of AQP4. Deletion of AQP4 intensified 1, 2-DCE-induced brain edema. 1, 2-DCE-induced dysregulation of miR-29b aggravates brain edema by directly targeting to AQP4 . Abstract: Overexposure to 1, 2-dichloroethane (1, 2-DCE) can induce brain edema, but the underlying mechanisms remain largely unknown. Aquaporin 4 (AQP4) is the most prevalent water channel in the brain, and the pool of AQP4 facilitates brain edema by controlling the inflow and clearance of brain water. MicroRNAs play an important role in the regulation of brain edema via RNA silencing and post-transcriptional regulation of gene expression. To explore the regulation role of AQP4 and microRNA in 1, 2-DCE-induced brain edema, Sprague-Dawley (SD) rats and AQP4 knockout CD-1 mice were exposed to 1, 2-DCE by inhalation for 7 days (0, 600, 1, 800 mg/m 3 ) and 28 days (0, 100, 350, 700 mg/m 3 ), respectively. The results showed that 1, 2-DCE induces brain edema, in both rats and mice, characterized by an increase in brain water content and vacuolations in the brain parenchyma and around the vessels of the cerebral cortex. Notably, 1, 2-DCE exposure can down-regulate AQP4 expression, in both rats and mice. Also, deleting AQP4 intensifies 1, 2-DCE-induced brain edema in mice. Meanwhile, microRNA-29b-3p (miR-29b) expression increases with 1, 2-DCE exposure, in both rats and mice. A negative correlation was found between the expression of miR-29b and AQP4 in vivo . Moreover, the negative regulation of miR-29b by direct targeting to AQP4 was confirmed by dual luciferase reporter assay in vitro . Taken together, our findings indicate that AQP4 plays an important role in balancing water content in 1, 2-DCE-induced brain edema. The dysregulation of miR-29b after 1, 2-DCE exposure can aggravate brain edema by directly suppressing the expression of AQP4.